Investigation of the impact behavior of steel and composite pipes with protective layer. (16th February 2017) - Anil, Özgür; Akbaş, S. Oğuzhan; Gezer, Onur; Yılmaz, M. Cem
Abstract : A free‐fall impact apparatus was used in this study to examine the behavior of steel and composite pipe systems designed with three different protective layers, considering both the efficiency and the energy adsorption capacity under impact loading. The three protective layers considered in this study are a granular soil layer of constant relative density and sand layers reinforced with geotextile and geogrid layers. The magnitudes of the impact loads as well as the resultant accelerations on the pipes were measured as a function of time during the experiments. Time histories of accelerations recorded in each test were used to calculate the displacements and loads on the pipes, which in turn led to estimates of the level of energy adsorbed by the protective layer systems. This enabled a fair comparison of the relative performance of each protective layer under impact load conditions. It was observed that all three protective systems contributed significantly to pipe safety. However, both the experimental results and the supporting finite element analyses indicate that the most successful pipe performance was achieved through the use of a geotextile‐reinforced soil layer. Furthermore, it was observed that the composite pipe has a higher energy adsorption capacity compared with the steel pipe, making it less vulnerable to impact forces under the same protection conditions.